Complex Abilities of Communicators and Specificity of Their Formation - Burnazova, Vera; Yunyk, Dmytro; Yunyk, Ivan; Yunyk, Tetiana; Kotova, Lina (Journal of History Culture and Art Research, 2019)
The complex abilities of communicators as non-innate, but the acquired universal system of psychophysical actions are regarded; they are aimed at creating a generalized image of the imaginary model of communicating information for recipients, not from relatively independent constructs, but from their united groups, as well as its implementation through the block utilization of communication skills. The psychological structure of these abilities, which consists of motivational-volitional, operational-procedural and content-reflexive components, is revealed. It is proved that the formation of complex communicator abilities requires the purposeful development of each of their components in the process of preparation for professional activities. Improvement of the motivational-volitional component of the indicated abilities is the activation of the desired types of motives, their awareness and regulation of the intensity of the existing emotions (preservation, amplification or relaxation). The prospect of improving the operational and procedural component of complex communicator abilities is traced by the achievement of the dominance of procedural motivation, which increases the efficiency of the implementation of not only thoughtful operations, but also the implementation of imaginary images through the block application of their constructs and communicative skills. The improvement of their content-reflexive component is carried out by the use of productive means of control of the process of preserving the expressiveness of differentiated constructs with the intermediate fixation of the imaginary created model of conveying information to recipients and the process of conscious and adequate assessment of the intermediate effectiveness of its communicative realization, which ensures that the right decisions are made.